General geology and soil erosion risk assessments using gis intergrations in Chin Tick farm, Gua Musang, Kelantan - Nur Hazmira Nawi (2013)
The geological mapping had been done in order to make observations of geology in the field. The detailed general geology, geomorphology and lithostratigraphy of the study area had been done to know the geology of the Chin Tick Farm, Gua Musang. There are consist of four type of lithology at the study area. there are acid intrusive, interbedded sandstone, siltstone and shale, limestone/marble and phyllite, schist and shale. Soil erosion is a growing problem especially in areas of agricultural activity where soil erosion not only leads to decreased agricultural productivity but also reduces water availability. Universal Soil Loss Equation (USLE) is the most popular empirically based model used globally for erosion prediction and control. Geographical Information System approach had been used to access soil erosion at the study area. Universal Soil Erosion Equation is used in order for erosion prediction and control. The soil erosion rate was determined as a function of land topography, soil texture, land use/land cover, rainfall erosivity, and crop management and practice in the study area. the average rainfall of the study area was found as 1697 mm and the soil erodibility, k-factor has factor range from 0.042 (ton.ha)(ha.hr/Mj.mm) to 0.0065 (ton.ha)(ha.hr/Mj.mm). The C factor was taken from land use map. The P factor was derived from land use map. Based on the GIS intergration, five classes of soil erosion risk had been determined. In the study area, the The first largest contributor of soil erosion in study area is agricultural activities, then urbanization and finally infrastructures.